Optimizing the Presidential Instruction on the National Single Social and Economic Database (DTSEN) in Social Protection Policy Reform: Toward the Eradication of Extreme Poverty in Indonesia - Ade Setiadi; Arief Nurcahyo (Jurnal Indonesia Sosial Sains, 2026)
The eradication of extreme poverty remains a major challenge in Indonesia, requiring effective social protection policies supported by accurate, integrated, and up-to-date beneficiary data. Previous social protection systems, particularly the Integrated Social Welfare Data (DTKS), have faced problems related to inclusion and exclusion errors, resulting in ineffective targeting of social assistance programs. To address these issues, the Indonesian government introduced Presidential Instruction No. 4 of 2025 concerning the National Single Social and Economic Database (DTSEN) as a strategic reform to strengthen data governance and improve poverty alleviation efforts. This study aims to analyze the optimization of DTSEN implementation in supporting social protection policy reform and accelerating the eradication of extreme poverty in Indonesia. This research employed a qualitative approach with a policy analysis and literature review design. Data were collected from government regulations, institutional reports, academic publications, and relevant international studies, which were analyzed using descriptive qualitative analysis. The findings indicate that DTSEN provides significant opportunities to improve social assistance targeting, increase budget efficiency, support evidence-based policymaking, and strengthen transparency and accountability in social protection programs. However, its implementation faces challenges, including data integration, infrastructure readiness, human resource capacity, privacy protection, and coordination among institutions. In conclusion, DTSEN represents an important transformation toward a more adaptive, accurate, and inclusive social protection system. Successful implementation requires continuous data validation, strong institutional collaboration, technological improvement, and active community participation to achieve the national goal of eliminating extreme poverty.